2007
DOI: 10.1007/s00221-007-1101-2
|View full text |Cite
|
Sign up to set email alerts
|

Learning effects on muscle modes and multi-mode postural synergies

Abstract: We used the framework of the uncontrolled manifold hypothesis to explore the effects of practice on the composition of muscle groups (M-modes) and multi-M-mode synergies stabilizing the location of the center of pressure (COP). In particular, we tested a hypothesis that practice could lead to a transition from co-contraction muscle activation patterns to reciprocal patterns. We also tested a hypothesis that new sets of M-modes would form stronger synergies stabilizing COP location. Subjects practiced load rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 41 publications
6
58
2
1
Order By: Relevance
“…Note that a different "atypical" set of M-modes has been reported in studies when the subjects performed relatively natural tasks while standing on a board with a decreased support area (Krishnamoorthy et al 2004b;Asaka et al 2007). Those M-modes involved muscle cocontraction that could be interpreted as a change in the range of joint angle values within which the muscle pairs could be active simultaneously without a change in the body reference configuration.…”
Section: Hierarchical Control Of Posture and The Reference Configuratmentioning
confidence: 91%
See 2 more Smart Citations
“…Note that a different "atypical" set of M-modes has been reported in studies when the subjects performed relatively natural tasks while standing on a board with a decreased support area (Krishnamoorthy et al 2004b;Asaka et al 2007). Those M-modes involved muscle cocontraction that could be interpreted as a change in the range of joint angle values within which the muscle pairs could be active simultaneously without a change in the body reference configuration.…”
Section: Hierarchical Control Of Posture and The Reference Configuratmentioning
confidence: 91%
“…Combined with previous reports, they also indicate that M-mode composition can vary in a task-specific way. Note that another group of M-modes, co-contraction modes, have been reported in studies of whole-body tasks performed in unusual conditions (Krishnamoorthy et al 2004); with practice, these M-modes tend to be replaced with "pushback" and "push-forward" modes (Asaka et al 2007). …”
Section: Composition Of Muscle Modesmentioning
confidence: 94%
See 1 more Smart Citation
“…Several recent studies have shown that the composition of M-modes may change depending on the task and also at different times before and after a postural perturbation (Asaka et al 2008;Krishnamoorthy et al 2004;. Until now, there have been no attempts to compare synergy indexes computed for the same data set based on different sets of M-modes.…”
mentioning
confidence: 99%
“…Na prática clínica da Fisioterapia, é comum o treino de equilíbrio com pacientes em pé sobre superfícies estáveis e instáveis (colchonetes e espumas) 13 , ao mesmo tempo em que esses pacientes recebem um distúrbio postural externo, como, por exemplo, pegar uma bola arremessada pelo terapeuta 13 . Porém, como mencionado, APAs e APCs podem ser modificados de acordo com a característica das tarefas e da condição de estabilidade postural [7][8][9][10][11][12] . Desta forma, as estratégias de ajuste postural sob esse tipo de intervenção fisioterapêutica merecem investigação adicional.…”
Section: Pesquisa Originalunclassified